KEKERASAN VERBAL SUAMI TERHADAP ISTRI PADA KELUARGA PRA SEJAHTERA PERSPEKTIF PIDANA - Sutriyono Sutriyono; Nur Mu'minah (SAMAWA, 2025)
This research aims to analyze Verbal Violence of Husband Against Wife inPre-Prosperous Family from Criminal Perspective, where individuals orfamilies have not been able to meet the basic needs of life properly. Using aqualitative method with a literature study, data was collected from varioussources, including scientific journals and relevant laws and regulations. Theresults show that verbal violence, although often considered trivial, has asignificant psychological impact on victims, including trauma and mentalhealth disorders. This verbal violence is a serious violation of human rightsand is regulated in Law No. 23/2004 on the Elimination of DomesticViolence. This research emphasizes the importance of understanding thefactors that cause verbal violence, such as economic conditions, socialnorms, and psychological factors, to formulate more effective preventionstrategies in addressing the issue of domestic violence.Keyword:Verbal Abuse, Husband And Wife, Pre-Prosperity,Crime